Invention engineering – a novel approach to support creativity in engineering, practice and research - Noennig, Joerg Rainer; Wiesenhuetter, Sebastian (Національний технічний університет "Харківський політехнічний інститут", 2019)
In engineering education, practice and research, a central issue is how traditional thought patterns can be broken up by creative tools and impulses. This paper presents the outline for a method that supports the discovery of new sources of inspiration in search fields such as literature, film, fine art or music, and enables engineers to generate design alternatives in high speed and quantity. For this end, techniques from the design sciences, creativity and innovation research as well as digital information and knowledge technologies are reviewed and integrated into the conceptual approach of Invention Engineering. The aim is to develop and validate a process which provides artistic inspirations to engineers and is supported by algorithmic creativity and association tools. Thus four separate research challenges need to be addressed: a) Analysis of creative processes in engineering disciplines (inspiration, association, ideation, innovation) and their comparison to "Creative Patterns" of other domains; In addition, visions of the past and the socio-technical framework conditions of their implementation need to be explored in order to establish a model for the validation of the overall Invention Engineering method; b) Development of an "Inspiration Mining" method for obtaining creative impulses from non-engineering areas (e.g. literature, music, visual arts, film et al.); Respective search results need to be referenced with a semantic model and processed in a knowledge system (Idea Bank), which – as a kind of associative search engine – provides input for idea generation; c) Translation of established creativity and innovation research into an "Idea Engine" for generation of a large number of productive ideas; This can be done through combinatorial algorithms and methods of remote association, textual and visual-spatial idea matrices, that provide a fertile basis for radically new design and engineering ideas; d) Integration of the separate methods into a coherent process and validation of the creative support effect of the generated innovations by means of engineering psychology. This can be done on the basis of selected visionary ideas from the past (e.g. science fiction) that can be simulated on the basis of their associative foundations and implementation probabilities.

В галузі інженерної освіти, практики та досліджень центральним питанням є те, як традиційні моделі мислення можуть бути розбиті творчими інструментами та імпульсами. В статті представлено схему методу, який підтримує відкриття нових джерел натхнення у таких сферах пошуку, як література, кіно, образотворче мистецтво чи музика, і дозволяє інженерам створювати альтернативні дизайни швидко та у великій кількості. З цією метою методи з дизайнерських наук, творчості та інновацій, а також цифрової інформації та технологій пізнань переглядаються та інтегруються в концептуальний підхід винахідницької інженерії. Метою є розробка та підтвердження процесу, який забезпечує художнє натхнення інженерам та підтримується алгоритмічними інструментами творчості та асоціації. Таким чином, потрібно вирішити чотири окремі проблеми дослідження: а) аналіз творчих процесів в інженерних дисциплінах (натхнення, асоціація, ідеї, інновації) та їх порівняння з «креативними моделями» інших областей; крім того, необхідно вивчити бачення минулого та соціально-технічні рамкові умови їх впровадження, щоб встановити модель для валідації загального методу винахідницької інженерії; б) розробка методу "Натхнення для натхнення" для отримання творчих імпульсів з інженерних галузей (наприклад, літератури, музики, образотворчого мистецтва, кіно та ін.); відповідні результати пошуку повинні посилатися на семантичну модель і оброблятися у системі знань (Банк Ідеї), яка, як своєрідна асоціативна пошукова система, дає внесок для генерування ідеї; в) переклад встановлених досліджень творчості та інновацій у "двигун ідеї" для генерації великої кількості продуктивних ідей; це можна зробити за допомогою комбінаторних алгоритмів та методів віддаленої асоціації, текстових та візуально-просторових матриць ідей, які дають плодовиту основу для радикально нових дизайнерських та інженерних ідей; г) інтеграція окремих методів у цілісний процес і перевірка ефекту творчої підтримки створених інновацій засобами інженерної психології; це можна зробити на основі відібраних уявних ідей із минулого (наприклад, наукової фантастики), які можуть бути змодельовані на основі їх асоціативних основ та ймовірностей реалізації.
Винахідницька інженерія - новий підхід до підтримки творчості в інженерії, практиці та дослідженні
Keywords: invention engineering; creative technique; innovation management; винахідницька інженерія; креативні методи; генерація ідей